An Internet of Things-based Automatic Medicine Consumption Reminder Box - Fauzan, Muhammad; Paramytha, Nina (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Because of age or doing too many activities at home, we often forget the obligation to consume routine medications that we should take that should be scheduled and the doses that have been determined. Therefore, the author wants to develop a tool that helps us consume drugs regularly and regularly. The medicine box uses ESP32 to integrate components such as ultrasonic sensors, loadcells, RTC, sound sensors, and ESP32 modules. Ultrasonic sensors are used to open and close the medicine box automatically, loadcell sensors to find out the condition of the rest or weight of the drug in the box, and RTC sensors as a timer to schedule drug consumption set on ESP32 which will send data on drug consumption schedules, sound sensors to find out the location of the medicine box by clapping both hands so that the detector detects sound and sounds the buzzer, ESP32 module as a microcontroller and sender of all programs that will be sent via the user's telegram application drug box.